The Representation of Ideal Beauty in Advertising--A longitudinal study of No.7 - GU, ANQI (2017)
With the development of economy, advertising is evolving considerably beyond the use of simple techniques to propaganda the usefulness of products. Rather, it is moving to a more persuasive domain, which exists as an omnipresent element, pervading every aspects of contemporary social life and delivering certain meanings to human beings (Beasley & Danesi, 2002). Attractive model is one of the most dominant elements exist in ads that to some extent deliver values, aesthetic standards, life attitudes to audiences. According to the definition of beauty posited by Aristotle and Plato, either external beauty or internal beauty is hard to neglect that ideal beauty under this topic will contains two aspects, one for physical appearance and another for value indication, which is the first time to make a conjunction. In order to explore how ideal beauty is represented in advertisements, the research objectives are three-fold. Firstly, it wishes to explore in which way female beauty is represented in ads through values. Secondly, the second aim is to examine if ideal beauty is an eternal concept or it would change within time. Thirdly, the research is going to examine how various beauty types are described with values in ads. A content analysis with 55 Boots No.7 TV commercials altogether in which 28 ads in 20th century and 27 ads in 21st century is employed in this research. The fixed categorization will utilize both Solomon (1992)’s beauty type model and Pollay (1983)’s value categorization system. Results show that female beauty is mostly accord with the social background that values are represented by expressing the intrinsic will of women in different period and physical beauty is not a constant figure which could shown by the alternative beauty types that are employed based on cultural gatekeepers’ aesthetic value. Freedom and Vain are the most frequently used values in both periods, however, the essence and representative way are different that the latter ones focus more on independence and is illustrated more deeper while the former ones indicate women’s dependence on male. Meanwhile, Classic Beauty, Feminine and Exotic are types most prevailing in No.7 commercial, which is in line with other experts’ study, the new finding is that Feminine and Sensual are in fact not same with Classic Beauty and Exotic. Besides, based on No.7 TV commercials, there is a match-up between beauty type and values, it is indicated that values could also used to understand beauty type, which are beneficial for practitioners to reinforce the brand image and is accord with No.7’ positioning.